Seroprevalence of HSV-1 and HSV-2 antibodies in Canadian women screened for enrolment in a herpes simplex virus vaccine trial. (May 2013) - Gorfinkel, I S; Aoki, F; McNeil, S; Dionne, M; Shafran, S D; Zickler, P; Halperin, S; Langley, J; Bellamy, A; Schulte, J; Heineman, T; Belshe, R
Summary: Herpes simplex virus 1 and 2 (HSV-1 and HSV-2) infections continue to be among the most common and unrecognized sexually transmitted infections in the world. Although treatable, HSV-1 and HSV-2 infections remain incurable. Hence, there is interest in the development of a vaccine to prevent genital herpes. As part of a multicentre, randomized, placebo-controlled trial to test such a vaccine, healthy women 18–30 years were enrolled as volunteers in several Canadian centres between 2005 and 2007. This study reports the seroprevalence of HSV-1 and HSV-2 antibodies in this group. A total of 2694 adult female volunteers in Canada with no known history of herpes simplex were screened for HSV antibodies using Western blot assay (the gold standard for diagnosis of HSV) for potential participation in a randomized, double-blind efficacy field trial of a herpes simplex vaccine. This trial provides a unique opportunity to examine the prevalence of antibodies to HSV-1 and of antibodies to HSV-2 in women with no known history of herpes simplex infection. The prevalence of antibodies to HSV-1 and to HSV-2 is compared with that found in previous Canadian studies that focused on a more general population. The overall seroprevalence of antibody to HSV-1 was 43%; that of HSV-2 was 2.5% and seropositivity to both was 2%. The prevalence of antibody to both HSV-1 and to HSV-2 increased with age. Seronegativity to both HSV-1 and HSV-2 was 56% in participating centres with populations under 250, 000 and 46% in participating centres with populations over 250, 000. Significant racial differences in seropositivity to HSV-1 and to HSV-2 were noted. The likelihood of participants being seropositive to HSV-1 and to HSV-2 was found to increase with age and to positively correlate with the population of the city in which they resided. Hypotheses are proposed to account for differences in racial seropositivity to HSV-1 and to HSV-2.